Pay across EU Regions: Contributory Effects of Labor Markets and Regional Heterogeneity - Webber, Don J. (Journal of Income Distribution®, 2001)
This paper presents an investigation into the effects of regional labour market characteristics on the evolution of average pay across regions of the European Union. Using pooled time-series-cross-section regression analysis and data that corresponds to thirty-two regions between 1986-1994, regionally adjusted unemployment benefits and employment rates are identified as being statistically significant determinants of relative average regional pay over time. Unobservable regional heterogeneity is also identified as being an important contributory factor behind this evolution.